Myeloid‐derived suppressor cells increase and inhibit donor‐reactive T cell responses to graft intestinal epithelium in intestinal transplant patients. Issue 10 (17th April 2018) - Okano, Shinji; Abu‐Elmagd, Kareem; Kish, Danielle D.; Keslar, Karen; Baldwin, William M.; Fairchild, Robert L.; Fujiki, Masato; Khanna, Ajai; Osman, Mohammed; Costa, Guilherme; Fung, John; Miller, Charles; et al.
Abstract : Recent advances in immunosuppressive regimens have decreased acute cellular rejection (ACR) rates and improved intestinal and multivisceral transplant (ITx) recipient survival. We investigated the role of myeloid‐derived suppressor cells (MDSCs) in ITx. We identified MDSCs as CD33 + CD11b + lineage(CD3/CD56/CD19) − HLA‐DR −/low cells with 3 subsets, CD14 − CD15 − (e‐MDSCs), CD14 + CD15 − (M‐MDSCs), and CD14 − CD15 + (PMN‐MDSCs), in peripheral blood mononuclear cells (PBMCs) and mononuclear cells in the grafted intestinal mucosa. Total MDSC numbers increased in PBMCs after ITx; among MDSC subsets, M‐MDSC numbers were maintained at a high level after 2 months post ITx. The MDSC numbers decreased in ITx recipients with ACR. MDSC numbers were positively correlated with serum interleukin (IL)‐6 levels and the glucocorticoid administration index. IL‐6 and methylprednisolone enhanced the differentiation of bone marrow cells to MDSCs in vitro. M‐MDSCs and e‐MDSCs expressed CCR1, ‐2, and ‐3; e‐MDSCs and PMN‐MDSCs expressed CXCR2; and intestinal grafts expressed the corresponding chemokine ligands after ITx. Of note, the percentage of MDSCs among intestinal mucosal CD45 + cells increased after ITx. A novel in vitro assay demonstrated that MDSCs suppressed donor‐reactive T cell–mediated destruction of donor intestinal epithelial organoids. Taken together, our results suggest that MDSCs accumulate in the recipient PBMCs and the grafted intestinal mucosa in ITx, and may regulate ACR. Abstract : This study suggests myeloid‐derived suppressor cells may regulate acute cellular rejection in human intestinal and multivisceral transplantation.